Integrative Literature Review Examining Factors Affecting Patient Safety With Robotic‐Assisted and Laparoscopic Surgeries. Issue 6 (30th October 2018) - Mathew, Reshmi; Markey, Kathleen; Murphy, Jill; Brien, Brid O'
Abstract: Purpose: The purpose of this integrative literature review is to examine the evidence on factors affecting patient safety during robotic‐assisted and laparoscopic surgeries. Design: Systematic review of papers published between 2011 and 2016 that identified factors affecting safety during robotic‐assisted and laparoscopic surgeries, in the areas of colorectal, general, urological, and gynecological surgeries. Methods: A systematic literature search of the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, and Medline databases were performed. Twelve studies met the inclusion criteria outlining factors affecting safety in robotic‐assisted and laparoscopic surgeries. All 12 studies selected were quality appraised using the Critical Appraisal Skills Programme. Findings: Using thematic analysis, the outcomes from the 12 studies were categorized into three thematic categories. Intraoperative communication, teamwork, and disruptions are the key factors affecting patient safety during robotic‐assisted and laparoscopic surgeries. Conclusions: This integrative literature review identifies a dearth of evidence examining factors affecting patient safety during robotic‐assisted and laparoscopic surgeries. It draws attention to the complexities with teamwork, intraoperative communication and disruptions during robotic‐assisted and laparoscopic surgeries. Although robotic‐assisted surgery is generally seen as safe and effective, this review highlights the need for education and training that focuses on non‐technical skills development, disruption prevention and alertness in anticipating and minimising risk. Clinical Relevance: The evidence from this review identifies the different demands and diverse challenges in maintaining safety during robotic‐assisted and laparoscopic surgery. Although specific technical knowledge and skills are essential, this review highlights the importance of developing new ways of thinking with regard to assessment and management of disruptions, developing different teamwork patterns and communication skills, and overcoming challenges introduced during technology advanced surgeries. Nurses in the perioperative setting have an increased responsibility to continue professional development and remain vigilant to factors affecting patient safety. Early identification and management of factors leading to disruptions is imperative in the provision of safe perioperative care.